Kepentingan Indonesia Terhadap Ekspresi Budaya Tradisional Dalam Sumber Hukum Internasional Mengenai Hak Kekayaan Intelektual - Clara Ignatia Tobing; Jantarda Mauli Hutagalung (KRTHA BHAYANGKARA, 2023)
The Regime of Genetic Resources, Traditional Knowledge and Traditional Cultural Expressions (SDGPTEBT) is a different regime from the existing regime of intellectual property rights. The WIPO negotiations on SDGPTEBT were held in order to discuss the protection of the SDGPTEBT at the international level. One of the problems that emerged from these negotiations was the gap between developed and developing countries regarding the final form of the outcome of the negotiations. There is still no clarity regarding the status of the "international legal instrument" itself in terms of international law, whether the international legal instrument will be more inclined as a legally binding international agreement or a soft law that is not legally binding. In terms of the effect of the results of the negotiations on Indonesian national law, there is a need to promulgate a law sui generis regarding SDGPTEBT even though the results of the negotiations are still in the negotiation stage.